Etnobiologi Tradisi Melulur Suku Sasak Sade: Harmonisasi Manusia-Alam untuk Mendukung Kesehatan dan Kesejahteraan dalam Pariwisata Berkelanjutan (SDGs 3) di Pulau Lombok - Tatang Mujiandi; Zia Rona; Baiq Maria Ulfa; Lalu Hariska Rahidsyah; Anindita SHM Kusuma (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
The tradition of scrubbing the floor with cow dung in Sade Village, Central Lombok, is a Sasak cultural practice that has ecological, health, and symbolic functions. This study aims to uncover the value of local wisdom in the Melulur tradition and its contribution to public health and sustainable tourism. Using qualitative methods through observation, interviews, and document analysis, the study found that cow dung has antibacterial properties and can repel mosquitoes, thus supporting the quality of the home environment. This tradition also strengthens cultural identity and becomes a tourist attraction. The study results indicate that the Melulur practice plays a role in supporting SDGs 3 on health and well-being and strengthening local wisdom-based tourism in Sade Village.